The Phillips curve and long-term unemployment - Ricardo Llaudes (European Central Bank (ECB), 2005)
This paper studies the role of long-term unemployment in the determination of prices and wages. Labor market theories such as insider-outsider models predict that this type of unemployed are less relevant in the wage formation process than the newly unemployed. This paper looks for evidence of this behavior in a set of OECD countries. For this purpose, I propose a new specification of the Phillips Curve that contains different unemployment lengths in a time-varying NAIRU setting. This is done by constructing an index of unemployment that assigns different weights to the unemployed based on the length of their spell. The results show that unemployment duration matters in the determination of prices and wages, and that a smaller weight ought to be given to the long-term unemployed. This modified model has important implications for the policy maker: It produces more accurate forecasts of inflation and more precise estimates of the NAIRU.
Keywords: C22; E31; E50; J64; 330; Kalman filter; Long-term unemployment; NAIRU; Phillips curve; Phillips-Kurve; Langzeitarbeitslosigkeit; Natürliche Arbeitslosenquote; Schätzung; OECD-Staaten